The potential of environmental benefits of urban agriculture and their future - Singamayum Ashif (African Journal of Environmental Economics and Management, 2022)
The population of cities in India continues to expand exponentially. It is predicted that by 2050, 55% of Indians will be living in urban areas. Traditional Agricultural Industry is challenged to keep pace with this as it is estimated that agricultural land capacity can increase by 2% only. The concept of Urban Farming has gained the serious attention of Planners and Academic communities in India. The combined issues of Population explosion, rapid urbanization and climate change are posing great threat to the Food Supply. Urban Farming is seen to have potential for cities to have at least some measure of Food Security. Urban farming is a process of using innovative scientific farming techniques to produce high yield and high quality of fresh organic food in very limited urban areas like terraces and balconies, all year –round. It is seen to have many advantages including non- dependence on vagaries of Climate, use of recycled water from Sewage and treated Wet waste as compost, proximity of producers to consumers, reduction of carbon footprints etc. The Concept of Urban Vertical Farm has been around since the 80’s but the Urban Farming Industry is not growing so fast. The main challenges seem to be Economic viability and Sustainability There is still a lack of any comprehensive knowledge and know- how in the public realm regarding practical aspects of Urban Farming. The Economic costs and viability for large scale urban Farming seems prohibitive. Thus, so far, the urban farming industry has not grown much.